Biochar’s Leacheates Affect the Abscisic Acid Pathway in Rice Seedlings Under Low Temperature - Yuan, Jun; Meng, Jun; Liang, Xiao; Yang, E; Yang, Xu; Chen, Wen-fu (Frontiers in Plant Science, 2021)
Organic molecules of biochar’s leacheates are known to increase the cold resistance of rice seedlings. Yet, it remains unclear whether the organic molecules of biochar leacheates can interact with the abscisic acid (ABA) signaling pathway associated with low temperature. This study used experiments and bioinformatics (molecular docking) to determine which of the organic molecules of biochar’s leacheates could influence the ABA signaling pathway. Specifically, we investigated whether these molecules affected ABA, a plant hormone linked to cold resistance. The contents of endogenous ABA and its precursor carotenoids were determined under low-temperature stress (10°C) and treatment with different concentrations of biochar leacheates. With increased leacheate concentrations, the endogenous ABA and carotenoid contents also increased, as did the expression of ABA- and cold-related genes. When rice seedlings were instead treated with exogenous ABA, it also affected the above-measured indexes; hence, we surmised that certain water-soluble organic molecules of biochar could exert a similar effect as ABA. We first used gas chromatography/mass spectrometry (GC/MS) to identify the organic molecules in the biochar extract, and then we used molecular docking software Autodock to show how they interact. We found that the molecule (1R, 2R, 4S)-2-(6-chloropyridin-3-yl)-7-azabicyclo(2.2.1)heptane was simplified, as Cyah could dock with the ABA receptor protein OsPYL2 in rice, which shows Cyah in biochar is probably an analog of ABA, with a similar function. Based on these results, we conclude that organic molecules of biochar’s leacheates could enter into rice plants and interact with ABA-related proteins to affect the ABA signaling pathway, thereby improving the cold stress resistance of plants.